Extrapulmonary TB or sarcoidosis associated with TB? Case report - Costa, Gabriel Domingues (2018)
Objectives: The present report aims to discuss the differential diagnosis between tuberculosis and sarcoidosis. Case description: The case of a 25-year-old male patient who developed granulomatous arthritis and osteomyelitis with nonnecrotizing granulomatous inflammation suggesting a sarcoidosis. Twenty-four months before this report, he had positive laboratory results to pulmonary tuberculosis, however, he was not treated. Conclusion: This case report demonstrates how necessary is the follow-up of patient after the performance of a diagnostic testing to tuberculosis, and the challenge to confirm a diagnosis of sarcoidosis in a patient with tuberculosis.